Size-mediated onset of genetically determined maturation in the platyfish, Xiphophorus maculatus - Sohn, Joel Jay (1977)
A single sex-lined gene that controls the maturation process had previously been identified in Xiphophorus maculatus. It was presumed that this gene controls the age of onset of maturation. We demonstrate that the gene is either activated or not inhibited from activity by the attainment of a critical weight rather than age.